152k views
4 votes
3(x+1)=2(x-1) solve for x

User RnR
by
5.0k points

2 Answers

4 votes
x=-5
3(x+1)=2(x-1)
3x+3=2x-2
x=-5

If you still don’t understand, the picture has the more detailed work
3(x+1)=2(x-1) solve for x-example-1
User CVO
by
6.3k points
4 votes

Answer:

x = -5

Explanation:

3(1 + x) = 2(x + -1)

(1 * 3 + x * 3) = 2(x + -1)

(3 + 3x) = 2(x + -1)

Reorder the terms:

3 + 3x = 2(-1 + x)

3 + 3x = (-1 * 2 + x * 2)

3 + 3x = (-2 + 2x)

Solving :the equation

3 + 3x = -2 + 2x

add '-2x' to each side of the equation.

3 + 3x + -2x = -2 + 2x + -2x

Combine like terms: 3x + -2x = x

3 + x = -2 + 2x + -2x

combine like terms: 2x + -2x = 0

3 + x = -2 + 0

3 + x = -2

Add '-3' to each side of the equation.

3 + -3 + x = -2 + -3

Combine like terms: 3 + -3 = 0

0 + x = -2 + -3

x = -2 + -3

Combine like terms: -2 + -3 = -5

x = -5

divide each side by '1'.

x = -5

User Kishor Bikram Oli
by
5.8k points